2020
DOI: 10.1039/c9sc04964a
|View full text |Cite
|
Sign up to set email alerts
|

Resolving alternative organic crystal structures using density functional theory and NMR chemical shifts

Abstract: DFT optimisation often resolves conflicting crystal structure determinations, with NMR shifts helping in cases where optimisation diverges to different structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…This survey of repeat structure determinations in the CSD found that over 20% of 3132 pairs of alternative structures for the same system exhibited structural differences (mostly of hydrogen atoms) greater than 0.25 Å (i.e. significantly larger than would be expected from experimental uncertainties) [313]. DFT geometry optimisation resolved these differences in most cases, but in other cases the alternative structures solutions minimised to distinct structures.…”
Section: Validation Of Structures From Single-crystal Xrd Datamentioning
confidence: 98%
“…This survey of repeat structure determinations in the CSD found that over 20% of 3132 pairs of alternative structures for the same system exhibited structural differences (mostly of hydrogen atoms) greater than 0.25 Å (i.e. significantly larger than would be expected from experimental uncertainties) [313]. DFT geometry optimisation resolved these differences in most cases, but in other cases the alternative structures solutions minimised to distinct structures.…”
Section: Validation Of Structures From Single-crystal Xrd Datamentioning
confidence: 98%
“…The validation of diffractographic structures is based on the comparison between experimentally measured NMR parameters with those calculated with DFT methods. This process was proven effective at resolving ambiguities related to the molecular structure [ 31 ], to choose between alternative proposed structures [ 32 , 33 ], and to refine them through optimization of atom positions in the unit cell [ 34 , 35 , 36 , 37 ]. Although optimization of hydrogen atoms usually has the biggest effect, changes in heavy atom positions obtained through full optimization of the molecule sometimes results in improved agreement with experimental NMR data.…”
Section: Introductionmentioning
confidence: 99%
“… 43 , 66 Table S2 states the energy differences for the different DFT-D calculations, with DFT having previously been used to evaluate different crystal structures. 67 69 Note that for TFM RT , with the less or more highly occupied sites only as starting points, i.e. C4–NH–C5–C6 torsional angle of −7.8 and 28.6° (labeled as A and B), respectively, there remains an energy difference of only 0.8 kJ/mol after optimization of all atomic positions and unit cell parameters.…”
Section: Results and Discussionmentioning
confidence: 99%